Respuesta :

Wolfyy

Hey there,

The squeeze theorem shows if [tex]f(x)\leq g(x)\leq h(x)[/tex] for all real numbers [tex](-\infty,~\infty)[/tex] then f(x) = h(x) but g(x) has to equal that as well.

Let's say we have [ [tex]\lim_{n \to \infty} (\frac{cos~x}{x})[/tex] ]

~Apply the theorem

Note that [ [tex]-1 \leq cos~x \leq 1[/tex] ] and [ [tex]\lim_{n \to \infty} (-\frac{1}{x})\leq \lim_{n \to \infty} (\frac{cos~x}{x})\leq \lim_{n \to \infty} (\frac{1}{x})[/tex] ]

~Apply the infinity property to every side but the middle

[tex]\lim_{n \to \infty} (-\frac{1}{x}) = 0[/tex]

[tex]\lim_{n \to \infty} (\frac{1}{x}) = 0[/tex]

So... [tex]\lim_{n \to \infty} (\frac{cos~x}{x})=0[/tex]

Best of Luck!

ACCESS MORE